Torrefaction of Almond and Walnut Byproducts - McCaffrey, Zach; Torres, Lennard; Chiou, Bor-Sen; Ferreira, Saulo Rocha; Silva, Luiz Eduardo; Wood, Delilah F.; Orts, William John (Frontiers in Energy Research, 2021)
While the US nut industry is growing, markets for nut by-products, particularly nutshells and tree prunings, have not kept pace. Torrefaction is a thermochemical process used to improve physicochemical properties of biomass for energy and other applications. The goal of the paper was to characterize the effects of a range of torrefaction conditions on the properties of nut by-product feedstock. The process consists of thermal treatment of biomass at a temperature between 200 and 300°C in the absence of oxygen, where final material properties of the torrefied biomass depend on the temperature, heating rate, and residence time. In general, torrefied biomass exhibits higher hydrophobicity and calorific value with reduced moisture absorption compared to untreated biomass, making it an ideal fuel source for energy applications compared to raw biomass. In this study, almond shells of soft, semi-soft, and hardshell varieties, as well as walnut shells and almond wood, were torrefied at two different temperatures (230 and 290°C) and three different residence times (20, 40, and 60 min) in order to characterize the physicochemical properties. The thermal behavior of raw and heat-treated biomass was investigated by TGA analysis, elemental analysis, pH, helium pycnometry, FTIR spectroscopy, and dynamic vapor sorption analysis.